Microwave-Assisted Chemistry: A Brief Overview - Rajni Mohil; Iqbal Singh (Advancements in Science and Technology: Paving the Way to a Sustainable Future, 2025)
The method for carrying out chemical reactions has changed as a result of advanced developments in microwave chemistry. This cutting-edge field uses microwave radiation to improve chemical reactions, leading to shorter reaction times, higher product yields, and more economical energy use. The use of microwaves in chemistry has gained popularity over the last few decades because of their many advantages over conventional heating methods. This Chapter explores the foundational ideas of microwave chemistry, the underlying mechanisms, real-world applications, benefits, and possible future advancements.